Integrating streamer and ocean-bottom seismic data AND OCEAN- for sub-basalt imaging on the Atlantic margin - Lau, K. W. H.; White, R. S.; Christie, P. A. F. (Petroleum Geoscience, 2010)
Stacked basalt flows cover much of the NW European continental margin, including potentially prospective sediments of the Faroes shelf. Such flows attenuate seismic energy, hindering sub-basalt structural imaging which is critical for both exploration and tectonic studies. Low-frequency, long-offset reflection surveys have yielded improved images below top basalt, while coincident ocean-bottom seismometer (OBS) data have mapped low velocity zones (LVZ) from tomographic inversion. Image correlation in a common depth domain is challenged by low spatial resolution of the tomographic image, the absence of turning rays in a LVZ and the lack of wide-angle arrivals in the reflection data. We integrate densely sampled reflection data with deep velocities from OBS data to give a common velocity model in a new, iterated, pre-stack depth-migration workflow using complementary constraints from the two datasets. The matched velocity model and depth image enable interpretation of (i) a uniform flood basalt sequence, 2–4 km thick beneath the Fugloy Ridge, with velocities correlating with those in the Lopra 1/1A borehole and (ii) a sub-basalt LVZ with chaotic reflections corresponding to sill-intruded, probably syn-rift sediments. Such a workflow could be extended to targets beneath high velocity salt or basalt and could provide constraints for 3D datasets.